A Rare Cause of Left Ventricular Assist Device (LVAD) Obstruction: Left Atrial Dissection - Hulman,Michal (2017)
Abstract Left atrial dissection is a rare factor that may cause left ventricular assist device obstruction. Prompt diagnosis and surgical repair are essential. This case report describes our experience and a successful surgical management in a patient after HeartMate 3 implantation and mitral valve inflow obstruction due to a left atrial dissection.